Students’ Learning Anxiety - Fitri Rayani Siregar; Winda Siska Perwana (English Education : English Journal for Teaching and Learning, 2020)
The aim of this research was to know students’ learning anxiety at VIII grade students of SMPN 2 Padangsidimpuan. Learning anxiety is one of the negative factors that affect the language learning process. This research employed descriptive method. The population of this research was the eighth grade students of SMPN 2 Padangsidimpuan. The total sample is 74 students taken by using random sampling. The researcher used 33 items of questionnaire for learning anxiety which adopted from Foreign Language Classroom Anxiety Scale (FLCAS) was developed by Horwitz and Cope. Questionnaire items were analyzed based on several indicators namely communication apprehension, fear of negative evaluation, test anxiety, English classroom anxiety. The score determined whether the anxiety level is very anxious level, anxious, midly anxious, relaxed and very relaxed level. The result showed that the VIII grade students of SMPN 2 Padangsidimpuan was in very anxious category. It was proved by the students’ acquisition score which the highest score was 158, the lowest score was 98 and mean score was 130,45. The finding could be conclude that generally students categorized into very anxious level.